PROBLEMATIKA PEREKRUTAN ANAK DALAM KONFLIK BERSENJATA DAN PERMASALAHANNYA DI INDONESIA - muh risnain (Universitas Lampung, 2014)
The issue of children recruitment in armed conflict will come into contact with the regime of International Law; International Humanitarian Law, International Human Rights Law, International Criminal Law and International Labor Law. The settings in the various legal regimes still leave problems related to the first, there is no uniformity about the minimum age of children who can be recruited as a child, whether 15 or 18 years old? second, legal obligations for the state does not have the same legal force between the obligations that just becomes commemoration to the state or the compulsory obligation. Keywords: Children Recruitment, Armed Conflict.